Bird Sounds Psychological Restorative Effect on The Visitors of Bogor Botanical Garden - Yuriko Asahiro; Arzyana Sunkar; Jarwadi Budi Hernowo (Bogor Agricultural University, Indonesia, 2023)
Stress can be defined as psychological and physical tension caused by physical, emotional, social, economic, and occupational, events, or experiences that are difficult to manage or endure. Bird sounds can be a potential solution to reduce stress levels. This study aimed to analyze the effect of bird sounds as a stress restorative on Bogor Botanical Garden visitors. A survey of 100 visitors of Bogor Botanical Garden was conducted based on the Perceived Stress Scale and Perceived Restorativeness Soundscape Scale. Data on respondent characteristics were analyzed using descriptive analysis, the relationship between stress levels and perceived stress restorative effect of bird sound was analyzed using Pearson correlation analysis. The analysis showed that 78% of respondents had moderate to high perceived stress levels and 98% of respondents rated the degree of restoration from bird sounds to be moderate to high. The correlation analysis revealed a negative relationship between the stress level and bird sounds' perceived restorative effect. The older the respondents and the more frequently they visited Bogor Botanical Garden, the higher the perceived stress restorative effect from bird sound.